Influence of organic and inorganic source of nutrients on physico-chemical attributes of fig (Ficus carica L.) cv. Dinkar (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted during 2023-24 to evaluate the impact of organic  and inorganic nutrients on the physico-chemical attributes of fig cv. Dinkar. The  highest fruit size, including length (5.31 cm), width (5.42 cm), fresh fruit weight  (44.38 g), dry fruit weight (21.48 g), fruit volume (45.70 cc), and specific gravity  (0.970), were observed in plants applied with 75% NPK + 25% Poultry manure.  Additionally, the highest values for TSS (18.86° Brix), reducing sugars (17.60%),  non-reducing sugars (1.29%), total sugar (18.90%), and TSS/Acid ratio (93.21) were  also recorded with 75% NPK + 25% Poultry manure. The lowest acidity (0.24%) was  found in plants treated with 75% NPK + 25% Poultry manure, while the highest  acidity (0.24%) was noted in those treated with 75% NPK + 25% Vermicompost. The  highest ascorbic acid content (13.30 mg/100g pulp) was also observed in the 75%  NPK + 25% Poultry manure treatment.
Keywords: Physico-chemical attri butes; inorganic nutrients; organic manures; fig; Dinkar